1965
DOI: 10.1001/archinte.1960.03860170080017
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pulmonary Aspergilloma With Amphotericin B

Abstract: treatment of bronchopulmonary aspergillosis have been reported following the administration of nystatin by aerosol1 as well as oral intake of large doses of potassium iodide.2 Parenteral injection of stilbamidine 3 and, more recently, amphotericin B 4,5 have also been considered to be successful in isolated cases. However, clinical effectiveness against deep-seated fungous diseases has been accompanied by a variety of disturbing side effects and evidence of toxicity during intravenous infusion of the drug 6,7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 10 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…A review performed by Benhamed and Woelffle found adjuvant amphotericin B did not affect morbidity or survival in post-surgical patients [36]. Furthermore, the potential complications associated with amphotericin B, particularly nephrotoxicity, makes this option unfavorable [37]. Within recent years, aerosolized amphotericin B administration through a nebulizer has shown promise at treating pulmonary aspergillosis and may be effective as a prophylaxis for invasive pulmonary aspergillosis in high-risk patients [38][39][40][41][42].…”
Section: Amphotericin Bmentioning
confidence: 99%
“…A review performed by Benhamed and Woelffle found adjuvant amphotericin B did not affect morbidity or survival in post-surgical patients [36]. Furthermore, the potential complications associated with amphotericin B, particularly nephrotoxicity, makes this option unfavorable [37]. Within recent years, aerosolized amphotericin B administration through a nebulizer has shown promise at treating pulmonary aspergillosis and may be effective as a prophylaxis for invasive pulmonary aspergillosis in high-risk patients [38][39][40][41][42].…”
Section: Amphotericin Bmentioning
confidence: 99%
“…Direct intracavitary administration of antifungal agents should be reserved for inoperable subjects. [11][12][13][14][15] However, the efficacy of intracavitary instillation of antifungals may depend upon the number and width of the drainage bronchi as well as on the mechanism of acceleration of fungus ball degradation. 16 Percutaneous intracavitary instillation of amphotericin B was performed in our case 4, but this therapy did not lead to a collapse of the fungus ball.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial embolization 99,100 or cavernoscopic evacuation of aspergilloma 97,101 may offer an alternative method of palliation in patients at high risk for resection. Medical treatment with intravenous amphotericin B or 5-flucytosine (5-FC) is ineffective, 94,102-104 but local endobronchial or intracavitary installation of amphotericin B, [103][104][105] sodium iodide, 85,106 natamycin, 102,107 miconazole, 108 ketoconazole 102 and 5-FC 109,110 have been tried with encouraging results, although prolonged installation and recurrence even with successful lysis of the aspergilloma are common.…”
Section: Aspergillomamentioning
confidence: 99%